# Yahoo Web Search

1. Sort by

1. ### Prove that G/N is Abelian iff ab(a^-1)(b^-1) ∈ N for all a,b ∈ G?

...normal. So aN*bN = ab(b^-1 N b)N = abNN = abN. G/N is abelian if and only if aNbN = bNaN which...

1 Answers · Science & Mathematics · 21/12/2010

2. ### please explain how to solve this geometry question?

...of a regular hexagon is 120° Angle FAB = 120° Angle ABN = 30° Angle BAN = 60° Hence angle FAN = 60°

3 Answers · Science & Mathematics · 05/11/2013

3. ### (5x-3)^3 use the binomial theorem to expand the binomial. formula is (a+b)^n=(n/0)a^r+(n/1)a^n-1 b+(n/2)a^n-2?

...n 1)aⁿ⁻¹b + (n 2)aⁿ⁻²b² + . . . + (n n-1)abⁿ⁻¹ + (n n)a⁰bⁿ (5x-3)³ = (3 0)(5x)³(-3...

1 Answers · Science & Mathematics · 04/10/2010

4. ### can any1 solve dis question for me?a/x - b/y=0and ab(b-square)/x + a(a square)b/y = a(sq) + b (sq)?

ya its easy,see all u hv 2do is dat put1/x=m and 1/y =n or which ever variable u like u will get am-bn=0 and ab*b*b-a*a*abn=a*a+b*b(this* is 4 multiply) solve the eq by equating coefficients.

1 Answers · Science & Mathematics · 09/05/2007

5. ### Trigonometry Help. 10pts to best answer.?

...'ll have to give you the options. If x is the angle ABN, then it is inverse tan (170 / 280) If x is the angle ANB...

1 Answers · Science & Mathematics · 12/06/2010

6. ### Prove that the median to the hypotenuse of a right triangle is one half the lenght of the hypotenuse?

...=included angle MNC [ since AB II MN, angle ABN= corresponding angle MNC = 1 right angle and angle MNB=180-90...

3 Answers · Science & Mathematics · 15/09/2011

7. ### How would you factor the following by grouping?

1) mx+my-nx-ny = (mx+my) + (-nx-ny) = m(x+y) + (-n)(x+y) = (x+y)(m-n) 2) 5cy-10c-2y+4 = (5cy-10c) + (-2y+4) = 5c(y-2) + (-2)(y-2) = (y-2)(5c-2) Can you catch on now?

3 Answers · Science & Mathematics · 22/01/2007

8. ### HELP!! math question help please!!! emergency?

... ax^2+by+c = 0 and a is b, b is a^2, and c is (a^2m-ABn).

4 Answers · Science & Mathematics · 05/10/2011

9. ### math problem?

... the right hand side, =(n^2+an+b)(n^2+an+b) =n^4+an^3+bn^2+an^3+a^2n^2+abn+bn^2+abn+b^2 =n^4+2an^3+(2b+a^2)n^2+2abn+b^2 By comparing...

2 Answers · Science & Mathematics · 12/07/2008

10. ### easy short answer geometrey?

... now we need to show that BN = CM consider triangles ABN and ACM here AB = AC as isosceles also AM = AN...

1 Answers · Science & Mathematics · 04/03/2008